2017
DOI: 10.20896/saci.v4i3.246
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Gandhian Thought to Corporate Responsibility

Abstract: Mahatma Gandhiji transformed contemporary capitalists amidst the criticism from leftist quarters that he was working for a compromise in the interests of the Indian bourgeoisie. The purpose of this paper is to present a forerunner of today’s conversations in the world about corporate social responsibility (CSR). Gandhiji not only befriended a number of businesspersons but also advised them to consider their role as a steward of their wealth and businesses that they held. We intend to substantiate his pious int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Just distribution meant equitable distribution of wealth according to one's needs. Last, in case of surplus wealth, Gandhian principles suggested that the individual retain only what was needed and use the rest for society's benefit in a judicious manner (Chakrabarty, 2015; Gopinath, 2005; Pulla et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Just distribution meant equitable distribution of wealth according to one's needs. Last, in case of surplus wealth, Gandhian principles suggested that the individual retain only what was needed and use the rest for society's benefit in a judicious manner (Chakrabarty, 2015; Gopinath, 2005; Pulla et al, 2017).…”
Section: Resultsmentioning
confidence: 99%